De- and Reterritorializing Identities: The Global Hip Hop Nation at Work in a Youth Hip Hop Recording Studio - Laniel-Tremblay, Édouard; Low, Bronwen (Critical Approaches Toward a Cosmopolitan Education, 2022)
This essay builds on previous studies of the “translanguaging” practices of members of the Montreal Hip Hop community (Low & Sarkar, 2014; Sarkar & Low, 2012) to explore how the challenge to linguistic norms in Quebec is also a challenge to social and identity norms. Our analysis is based on interviews with young musicians attending a community recording studio program in Montreal, the studio’s social media presence, and a track created in collaboration with youth in Paris. Through their relationships in the studio as well as their music, the youth de- and reterritorialize their identities (Papastergiadis, 2000), mobilizing local and global Hip Hop cultural references and communities in ways that challenge dominant narratives of belonging in Quebec and Canada.